Digital Posters For Digital Literacy Development - Sápiras, Fernanda Schuck; Bayer, Arno (INTERFACES DA EDUCAÇÃO, 2022)
This article deals with the construction of digital posters in the classroom, in teacher education, as a differentiated approach, exercising aspects related to Digital Literacy. The material of this article is an extraction of the activities and reflections of the fourth meeting, which followed the reading of the text referring to the concept of Digital Literacy, which served as a support to the development of digital posters analyzed in this article. The research is positioned in a qualitative bias and was developed during the training of mathematics teachers, composed of synchronous and asynchronous meetings. The training that gave rise to the analyzed data uses several technologies, with the bias of authorship and critical development defended in the concept of Digital Literacy. As a result, we have 12 digital posters that highlight aspects such as Digital Literacy skills and 5 criticalities, which is a central feature of the Digital Literacy concept. We understand that although the speech and position of the teachers, shown during the training, already indicate a reflection in their practice, when they realize that among the skills there is no order of importance or attributes, but all have their relevance and that they must be worked on. according to the possibilities offered by the activity and the teacher’s goal.